Additional clinical value of voxel‐based morphometric MRI post‐processing for MRI‐negative epilepsies: a prospective study. Issue 2 (1st June 2020) - El Tahry, Riëm; Santos, Susana Ferrao; Vrielynck, Pascal; de Tourtchaninoff, Marianne; Duprez, Thierry; Vaz, Geraldo Ribeiro; Raftopoulos, Christian; Choi, Joon Yul; Wang, Zhong Irene
ABSTRACT: Aims : Magnetic resonance imaging is of paramount importance in the presurgical evaluation of drug resistant epilepsy. Detection of a potentially epileptogenic lesion significantly improves seizure outcome after surgery. To optimize the detection of subtle lesions, MRI post‐processing techniques may be of essential help. Methods : In this study, we aimed to evaluate the detection rate of the voxel‐based morphometric analysis program (MAP) in a prospective trial. We aimed to study the MAP+ findings in terms of their clinical value in the decision‐making process of the presurgical evaluation. Results : We included, prospectively, 21 patients who had negative MRI by visual analysis. In a first step, results of the conventional non‐invasive presurgical evaluation were discussed, blinded to the MAP results, in multidisciplinary patient management conferences to determine the possible seizure onset zone and to set surgical or invasive evaluation plans. Thereafter, MAP results were presented, and the change of initial clinical plan was recorded. All MAP detections were reaffirmed by a neuroradiologist with epilepsy expertise. For the 21 patients included, mean age at the time of patient management conference was 26 years (SD 15 +/‐ years, range: 5–54 years). In total, 4/21 had temporal lobe epilepsy and 17/21 had extra‐temporal lobe epilepsy. MAP was positive in 10/21 (47%) patients and in 6/10 (60%) a diagnosis of focal cortical dysplasia was confirmed after neuroradiologist review, corresponding to a 28% detection rate. MAP+ findings had a clear impact on the initial management in 7/10 patients (7/21, 33% of all patients), which included an adaptation of the intracranial EEG plan (6/7 patients), or the decision to proceed directly to surgery (1/7 patients). Conclusion : MRI post‐processing using the MAP method yielded an increased detection rate of 28% for subtle dysplastic lesions in a prospective cohort of MRI‐negative patients, indicating its potential value in epilepsy presurgical evaluation.